Application of Biologically Active Substances for Storage of Oil Flax Straw - Kuzmina, T.О.; Yedynovych, M.B.; Berezovsky, Yu.V.; Bobyr, S.V.; Yevtushenko, V.V.; Rudenko, I.A. (Science and Innovation, 2024)
Introduction. In Ukraine, considerable volumes of raw flax material do not undergo preprocessing, which results in worsening of its quality, with the lapse of time. It is related to non-observance of agrotechnical requirements for collection, adverse weather conditions and other factors. Problem statement. The capacity of flax processing enterprises does not enable recycling the entire amount of raw material for a short period of time, therefore long-time storage is required. Environmentally safe, inexpensive preservation agents having inhibitory, bactericidal, and fungicidal properties can secure a high quality of oil flax straw. Purpose. The purpose of research is to study the influence of biologically active substances on the quality of oil flax straw and to determinate proper storage conditions. Materials and methods. For research, the oil flax varieties Vira, South Night, and Debut are selected. The tasks of research have been solved by means of theoretical and experimental methods used for preprocessing of raw material and in textile material science. The mathematical modelling of processes has been made in MathСad. Results. Influence of biologically active substances on storage of oil flax straw has been studied. The action mechanism of the studied preservation agents and dynamic changes in qualitative parameters of raw materials during long-time storage of straw have been determined. The statistical models of influence of oil flax straw storage conditions on the qualitative parameters of fiber have been obtained, optimal concentrations of preservation agents, conditions and terms of their effect have been established. Conclusions. Application of new environmentally safe bioactive substances for storing oil flax straw with a wide range of humidity has been substantiated.